Entry into entrepreneurship, endogenous adaption of risk attitudes and entrepreneurial survival - Matthias Brachert; Walter Hyll; Mirko Titze (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
Empirical studies use the assumption of stability in individual risk attitudes when searching for a relationship between attitude to risk and the decision to become and survive as an entrepreneur. We show that risk attitudes do not remain stable but face endogenous adaption when starting a new business. This adaption is associated with entrepreneurial survival. The results show that entrepreneurs with low risk tolerance before entering self-employment and increased risk tolerance when self-employed have a higher probability of survival than similar entrepreneurs experiencing a decrease in the willingness to take risks. We find the opposite results for entrepreneurs who express a higher willingness to take risks before becoming self-employed: in this case, a decrease in tolerance of risk is correlated with an increasing survival probability.
Keywords: D03; D81; M13; 330; Endogenous attitudes; Risk attitudes; Entrepreneurial survival; SOEP